Multiple cutaneous histiocytomas treated with lomustine in a dog. Issue 6 (25th June 2014) - Maina, Elisa; Colombo, Silvia; Stefanello, Damiano
<x xml:space="preserve">Abstract</x> Background Histiocytoma is a common benign neoplasm of young dogs. Multiple histiocytomas are rare. Surgical or medical treatment of solitary tumours is not required in the majority of cases because the tumour usually undergoes spontaneous regression. Therapy is required when lesions are persistent, recurrent, ulcerated or in uncomfortable locations. Hypothesis/Objectives To describe a case of canine multiple cutaneous histiocytomas treated with lomustine. Animal A 5‐year‐old miniature Pinscher dog was presented with multiple, disseminated, alopecic cutaneous nodules, with no associated systemic signs on initial presentation. Methods Histopathological examination of skin biopsies and immunocytochemistry of biopsy imprints were performed. Inguinal lymph node, liver, spleen and bone marrow cytological examination and abdominal ultrasound examination were also performed. Results The clinical, histopathological and immunocytochemical findings supported a diagnosis of canine multiple cutaneous histiocytomas. Owing to the increasing number and size of the nodules, medical treatment was initiated. Prednisone and ciclosporin resulted in worsening of lesions. Lomustine orally once monthly led to complete resolution followed by relapse. Metabolic disorders such as increased serum alanine transaminase and alkaline phosphatase activities were recorded, and therapy was stopped. Increase in size of the tumours, severe dullness and anorexia led the owner to elect euthanasia. Conclusions and clinical importance To the best of the authors' knowledge, this is the first case report of canine multiple cutaneous histiocytomas treated with lomustine. Lomustine is effective in histiocytic diseases, but adverse effects must be considered because they can be severe and life threatening.